Pengaruh Manajemen Talenta, Modal Sosial dan Employee Engagement Terhadap Kinerja Pegawai di Koperasi Serba Usaha Bintang Muda 88 Tana Toraja Cabang Makale - Yustin Yustin; Adriana Madya Marampa; Stefani M. Palimbong (Lembaga Pengembangan Kinerja Dosen, 2026)
This result aims to determine the Influence of Talent Management, Social Capital and Employee Engagement on Employee Performance at Bintang Muda 88 Tana Toraja Makale Branch is the voluntary behavior of employees that exceeds their formal duties and can support the smooth and effective running of the organization. This study uses a quantitative method. The research population is all employees at the Bintang Muda 88 multipurpose cooperative office, Makale branch, Tana Toraja Regency, as many as 30 people, and the sampling method uses a saturated sampling technique. Data collection is carried out through distributing questionnaires, and the data are analyzed using multiple linear regression tests with the help of the SPSS program. The results of the study indicate that the Influence of Talent Management, Social Capital and Employee Engagement on Employee Performance at Bintang Muda 88 Tana Toraja Makale Branch, This is evidenced by Thitung of 0. 472> Ttabel 0. 3739 has a significant number of 0. 000<0. 05. Similarly, Talent Management, Social Capital, and Employee Engagement have a positive effect on employee performance, as evidenced by a t-value of 0. 390 with a p-value of 0. 000. Therefore, the p-value is <0. 05. Simultaneously, Talent Management, Social Capital, and Employee Engagement also have a positive effect on Employee Performance at Bintang Muda 88 Tana Toraja, Makale Branch, as evidenced by an Fcount of 7. 532, Ftable of 3. 02, and a significance value of 0. 000 <0. 05.